Lost in things: an archaeologist's perspective on the epistemological potential of objects - Stockhammer, Philipp (Nature + culture, 2015)
In recent times, archaeology has seen continuously growing interest from neighboring disciplines desiring to capitalize on archaeology's experience with the evaluation of material culture. In order to be able to answer the questions now posed to our field of research, we have to be conscious of our methods and their epistemological potential. On the basis of a characterization of archaeological sources, this article focuses on four relevant fields of inquiry with regard to the archaeological analysis of an object, that is, its materiality, archaeological context, spatial distribution, meanings, and power. Moreover, I suggest that an integration of aspects of Bruno Latour's Actor-Network Theory will enable archaeologists to gain further insights into the complex entanglement of humans and objects in the past.